Assessment of Visual Function and Retinal Histology in a Snf2h Knockout Mouse Model - Cheng, Skyra (Université d'Ottawa / University of Ottawa, 2023)
Regulation of gene expression is required for embryogenesis and maintenance of the highly specialized and diverse neuron populations of the retina. Chromatin remodelling proteins control gene expression by modifying chromatin structure and are essential for many biological processes including mammalian development. The ATP-dependent chromatin remodelling protein Snf2h is highly expressed in the central nervous system, and pathogenic variants that cause neurodevelopmental abnormalities in the human population have recently been identified. This work aims to characterize the effects of Snf2h loss in the retina. Snf2h retinal conditional knockout (cKO) mice were generated using Snf2h-floxed mice and Chx10-Cre retina-specific Cre driver lines to ablate the Snf2h protein from the retina at embryonic day 10.5. Visual function was assessed via optomotor response-based testing and full-field scotopic electroretinography, and histological changes were examined via immunohistochemistry. Disease progression was tracked at one, two, three, and six months of age. Snf2h cKO mice showed a significant decline in visual function and exhibited retinal neuron loss compared to wildtype control littermates at all time points assessed. This work shows that the chromatin remodelling protein Snf2h plays an essential role in the structure and function of the retina.
Keywords: Snf2h; Vision; Gene regulation; Chromatin remodelling protein